Vulnerability as determinant of suicide among older people in Northern Indian states - Patel, Avanish Bhai (Frontiers in Psychology, 2022)
Older people are confronted with a myriad of challenges throughout the course of their lives in the present society. One of these is the issue of suicidal behaviour among people of older age. The current article understands the nature and examines the cause of mortality due to suicide among older people in later life. The author has applied the document analysis method. The information for the current research has been collected using the news content of various Indian newspapers, magazines, and news portals. The researcher has collated 60 occurrences of old age suicide from newspapers of Northern Indian states from March 2022 to June 2022. The study has indicated that there is a substantial rise in old age suicide due to the vulnerable condition of older people in late life. Moreover, the vulnerable condition of older people has led to the various factors instrumental in old age suicide as abuse in the family, chronic diseases, depression, poverty, and social rejection give rise to feelings of committing suicide among the older people.